Assessing Digital Transformation in Zakat Management Organizations in Indonesia - Tiara Salsabila Azzahra; Yunizar Yunizar; Muhammad Fathrul Quddus (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
The rapid growth of digital technology has reshaped zakat management, particularly in improving the efficiency, transparency, and accountability of collection, distribution, and reporting activities. In urban areas with strong digital penetration, Zakat Management Organizations (Organisasi Pengelola Zakat-OPZ) are increasingly encouraged to integrate digital systems into their operational activities. However, the continuing gap between zakat potential and actual collection suggests that the digital readiness of OPZ has not been fully optimized. This study evaluates the level of digital readiness among OPZ in Bandung City using the Zakat Management Organization Digital Readiness Index (IKDZ) developed by BAZNAS and Bank Indonesia. A descriptive quantitative approach was employed using primary data collected through structured questionnaires distributed to nine OPZ. The assessment covers four dimensions: digital infrastructure, utilization of digital technology, digital ecosystem and culture, and human resource competencies. The findings indicate that the digital readiness of OPZ in Bandung City is generally high. Eight OPZ are categorized as Digital Native, while one OPZ remains in the IT-Developing category. The reporting dimension achieved the highest readiness level, whereas the distribution and utilization dimensions still show several technical limitations. The study also identifies human resource competence and digital system integration as the main challenges affecting sustainable digital transformation in zakat management. ABSTRAK - Menilai Transformasi Digital pada Organisasi Pengelola Zakat di Indonesia. Perkembangan teknologi digital telah mendorong perubahan dalam pengelolaan zakat, terutama dalam meningkatkan efisiensi, transparansi, dan akuntabilitas penghimpunan, pendistribusian, serta pelaporan zakat. Di wilayah perkotaan dengan tingkat penetrasi digital yang tinggi, Organisasi Pengelola Zakat (OPZ) dituntut untuk mengintegrasikan sistem digital ke dalam aktivitas operasionalnya. Namun, kesenjangan antara potensi dan realisasi zakat menunjukkan bahwa kesiapan digital OPZ masih belum optimal. Penelitian ini bertujuan mengevaluasi tingkat kesiapan digital OPZ di Kota Bandung menggunakan Indeks Kesiapan Digital Zakat (IKDZ) yang dikembangkan oleh BAZNAS dan Bank Indonesia. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan data primer yang diperoleh melalui penyebaran kuesioner terstruktur kepada sembilan OPZ. Penilaian dilakukan terhadap empat dimensi, yaitu infrastruktur digital, pemanfaatan teknologi digital, ekosistem dan budaya digital, serta kompetensi sumber daya manusia. Hasil penelitian menunjukkan bahwa tingkat kesiapan digital OPZ di Kota Bandung tergolong tinggi. Delapan OPZ berada pada kategori Digital Native, sedangkan satu OPZ termasuk kategori IT-Developing. Dimensi pelaporan menunjukkan tingkat kesiapan tertinggi, sementara dimensi pendistribusian dan pendayagunaan masih menghadapi beberapa keterbatasan teknis. Penelitian ini juga menunjukkan bahwa kompetensi sumber daya manusia dan integrasi sistem digital menjadi tantangan utama dalam mendukung transformasi digital pengelolaan zakat yang berkelanjutan.